Research on the Characteristics and Influence Factors of Autumn Continuous Rain in Qinghai Province - Yang, Hanwei; Shen, Hongyan; Ma, Yue; Yang, Yawei; Wang, Xiaojuan; Feng, Guolin (Frontiers in Earth Science, 2022)
Using daily precipitation data of national meteorological stations in Qinghai Province and reanalysis data, the main patterns of autumn continuous rain (ACR) are extracted, and key SST areas and circulation factors are searched for to analyze the possible effects on the seasonal and sub-seasonal predictability of ACR in Qinghai Province. The factors with strong precursors mainly include sea surface temperature (SST), Arctic vortex, and subtropical high. The influence of oceanic factors on ACR is relatively independent, while there is an interaction between atmospheric circulation factors. The precursors in spring are from the equatorial east-central Pacific for the main pattern with consistent precipitation distribution, and the Indian Ocean for the pattern with “saddle type” distribution. SST anomalies from the Pacific and Indian Oceans force different circulation patterns that can enhance meridional circulation over Europe-Asia and lead to different precipitation pattern of ACR. The signals from the Arctic vortex and subtropical high in June to July are indicative for ACR. The southward, westward and strong Arctic vortex, together with the south-westward extension of subtropical high over the Atlantic and Pacific can promote more ACR in Qinghai Province. Under the SST forcing and configuration of high and low latitude circulation, the meridional circulation continues to be weak, and the latitudinal circulation to be enhanced over the Eurasia in the early period, and the circulation pattern changes from type-W to type-C, which lead to positive anomaly of ACR in Qinghai Province.